Fast high‐resolution imaging method for wide‐band rotating targets. Issue 20 (19th September 2019) - Xiang, Hu; Li, Shaodong; Xiang, Long; Chen, Wenfeng; Yang, Jun
Abstract : To reduce the computation burden of inverse synthetic aperture radar on rotating targets imaging, a fast distributed simultaneous multiple orthogonal matching pursuit method is proposed in this study. In the proposed method, the distributed matching sparse representation model of the rotating targets is firstly established. Also then the total number of iterations is reduced by using multi‐atom recognition strategy. Simultaneously, the computational complexity of each iteration is also reduced through QR decomposition. High‐resolution image of the rotating targets can thus be obtained efficiently. Theoretical analysis and simulation results verify the effectiveness of the proposed method.